A matrix model towards CSR – moving from one size fit approach. Issue 2 (12th March 2019) - Jose, Saju; Venkitachalam, Krishna
Abstract : Purpose: Corporate social responsibility (CSR) research is often dominated in a western context. Perhaps, with the rapid expansion of organisations in the context of emerging economies, there is a pressing need for the development of a new dimension. Organisations operating in emerging markets must address the social challenges of serving low-income consumers and rural communities as part of their CSR strategy. The next era of CSR should look out for a period of experimentation and innovation as organisations advance their core business objectives by addressing existing social and environmental issues, which are dependent on market and industry settings. The purpose of this paper is the requirement of careful considerations when formulating the CSR framework for different industries and markets in the global business environment and this is the focus in this paper. Design/methodology/approach: The paper provides a review and certain limitations of the literature on the highly cited works such as stakeholder theory and Carroll's pyramid model. Following on, the proposed matrix model, related discussion of the four phases and associated propositions are explained in the paper. Finally, some concluding remarks on the need for a new look on CSR in the context of non-western markets are presented. Findings: In this paper, the authors introduce "The matrix model of CSR" as a starting attempt and a guideline in formulating the CSR approach across industry and countries, particularly illustrating in the context of diverse organisations in different sectors. However, this model is at a conceptual level and future research could allow empirical testing and refinement of the "matrix model" in different market and industry conditions. Originality/value: A CSR model for multiple organisational contexts would provide more insight for the relevant stakeholders regarding their CSR activities. Thus, this article attempts to suggest a CSR matrix model and it takes a phased approach by classifying the CSR activities based on the degrees of CSR and altruistic nature of activities that could be adapted for other industries as well as emerging economies.